A double-blind phase III trial of immunomodulating nutritional formula during adjuvant chemoradiotherapy in head and neck cancer patients: IMPATOX. Issue 6 (16th September 2020) - Boisselier, Pierre; Kaminsky, Marie-Christine; Thézenas, Simon; Gallocher, Olivier; Lavau-Denes, Sandrine; Garcia-Ramirez, Muriel; Alfonsi, Marc; Cupissol, Didier; de Forges, Hélène; Janiszewski, Chloé; Geoffrois, Lionnel; Sire, Christian; et al.
ABSTRACT: Background: In a previous phase II study an immunonutrient supplement was found to reduce severe acute toxicities for head and neck squamous cell cancer (HNSCC) patients treated with concomitant cisplatin and radiotherapy. Objectives: The primary objective of the present study was to evaluate efficacy of the same immunonutrient supplement on severe mucositis. Secondary objectives included tolerance, compliance to oral supplementation, chemotherapy interruptions and delays, quality of life, and progression-free survival (PFS) and overall survival (OS) at 1, 2, and 3 y. Methods: Between November 2009 and June 2013, 180 HNSCC patients eligible for adjuvant chemotherapy after surgery with curative intent were included in our double-blind phase III multicenter trial. They were assigned to receive oral supplementation (3 sachets/d) of either a formula enriched with l -arginine and omega-3 (n–3) fatty and ribonucleic acids (experimental arm), or an isocaloric isonitrogenous control (control arm), for 5 d before each of 3 cycles of cisplatin. Intention-to-treat (ITT) and per-protocol (PP) analyses were undertaken, along with subgroup analyses of ≥75% compliant patients, to compare the incidence of acute mucositis (Radiation Therapy Oncology Group and WHO scales) and 36-mo survival. Results: At 1 mo after terminating chemoradiotherapy (CRT), no differences were observed in the incidence of grade 3–4 mucositis between treatment groups, in the ITT, PP (172 patients), and subgroup (≥75% compliance, n = 112) analyses. The immunomodulating supplement did not significantly improve survival in the ITT and PP analyses at 3 y after CRT. Among ≥75% compliant patients, however, OS at 3 y was significantly improved in the immunomodulating formula group (81%; 95% CI: 67%, 89%) compared with controls (61%; 95% CI: 46%, 73%; P = 0.034), as well as PFS (73%; 95% CI: 58%, 83% compared with 50%; 95% CI: 36%, 63%; P = 0.012). Conclusions: Although this immunomodulating formula failed to reduce severe mucositis during CRT, the findings suggest that the long-term survival of compliant HNSCC patients was improved. This trial was registered at clinicaltrials.gov as NCT01149642.